2010
DOI: 10.1097/brs.0b013e3181c70fe3
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Transforaminal Lumbar Interbody Fusion for the Treatment of Degenerative Lumbar Diseases

Abstract: Minimally invasive TLIF as a management of 1-level degenerative lumbar diseases is superior to the traditional open procedure in terms of postoperative back pain, total blood loss, need for transfusion, time to ambulation, length of hospital stay, soft-tissue injury, and functional recovery. However, this procedure takes longer operative duration and requires close attention to the risk of technical complications. Longer-term studies involving a larger sample are needed to validate the long-term efficacy of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
189
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(199 citation statements)
references
References 24 publications
6
189
2
2
Order By: Relevance
“…The advantages associated with MI-TLIF might be attributed to less intraoperative dissection and retraction of paravertebral muscles [1,2,5]. Shunwu et al [6] found the minimally invasive group was associated with a significantly lower creatine kinase (a marker of muscle injury) level on the third postoperative day. Wang et al [7] observed no differences in postoperative serum creatine kinase levels between the MI and open groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The advantages associated with MI-TLIF might be attributed to less intraoperative dissection and retraction of paravertebral muscles [1,2,5]. Shunwu et al [6] found the minimally invasive group was associated with a significantly lower creatine kinase (a marker of muscle injury) level on the third postoperative day. Wang et al [7] observed no differences in postoperative serum creatine kinase levels between the MI and open groups.…”
Section: Discussionmentioning
confidence: 99%
“…First, with limited visibility and working space, MI-TLIF requires good familiarity of anatomy. Some surgeons have suggested that MI-TLIF could increase surgical time [6,7]. Secondly, to facilitate a minimally invasive approach, more X-ray exposure was used [4,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As proposed already in lumbar spine surgery, this might reduce the denervation of muscles and hospital stay [10,16,21,22,38,44] and reduces the increased complication rate following posterior or combined anterior-posterior approaches [37]. The disadvantage of the technique clearly resulted from stabilization-only character, which limits the indications.…”
Section: Discussionmentioning
confidence: 98%
“…In this context, multi-level posterior as well as combined anteriorposterior approaches to the cervical spine are proposed to be associated with increased incidence of perioperative complications [37]. Similar to stabilization procedures of the thoracolumbar spine with the objective to reduce access-related morbidity as muscular denervation and atrophy, length of hospital stay and blood loss [10,16,21,22,38,44], minimally invasive procedures for cervical instrumentation represent the next step to reduce accessrelated muscular trauma. Therefore, several authors reported minimally invasive posterior procedures for stabilization and decompression of the cervical spine [8,33,40,45].…”
Section: Introductionmentioning
confidence: 99%